RECONSIDERING SOME CULTURAL CONSTRAINTS IN THE IMPLEMENTATION OF COMMUNICATIVE ENGLISH LEARNING - FX Nadar (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2000)
English is perhaps the most important foreign language in Indonesia . It is used for communication in business with other countries and studied in schools from junior high school to university level . People in Indonesia study English for different reasons . Many of them study English because if they understand English well they will be able to improve their general knowledge . Others particularly university students and lecturers study English because English may help them develop their academic achievement . Other people who are active in tourism and hotel industries need to study English because they have to communicate regularly with people from other countries . Despite the fact that English has been extensively studied, many learners feel they cannot use it for daily communication . This brief essay attempts to explore the constraints, particularly from the cultural views, which may have reduced the success of learning English . Approaches to language learning have undergone changes. Celce-Murcia (1991 :5- 8), for example, describes the stages of 20